RIGHT TO EDUCATION. A CRITICAL ESSAY ON THE CONCEPT OF TRANSMISSION - Colella, Leonardo (Revista de Filosofía, 2023)
This essay seeks to develop a hypothesis that links the pedagogical relationship with the political relationship and their interaction for the construction and reproduction of an identical logic that crosses and surpasses various social fields. This hypothesis that relates the very foundation of education with the metaphor of the pedagogical triangle and that identifies in it a logic of production of inequality makes us rethink the approach of education as a right without first questioning various elements that support it, especially those linked to the concept of transmission.